Identity and the emergence of South African advertising esperanto: an interdisciplinary approach to multilingualism and the visual in advertising and information copy (Communicare: Journal for Communication Studies in Africa, 2022)
There is no formal regulation of language use in the advertising industry to correspond to thedeclared commitment to multilingualism in the South African Constitution. A trend in televisionadvertising, where language diversity, translation, and/or reconceptualisation are circumvented byconceptualising a visual message devoid of voice-over, is the subject of this article. The purposeis to consider the extent to which this practice undermines or contributes to the perception ofa homogeneous marketplace and advertising language/esperanto. Visual texts provide a richalternative, but carry the inherent burden of the intermingling of text and subtext not conveyed bymeans of language. The suggestion is that this global homogenising trend for target audiences,developed in advertising copy, has since transcended advertising parameters to include all kindsof copy. Language as marker of culture is being written out of the definition of cultural specificityas one of the primary means of identifying target audience. By merging their expertise in criticallinguistics, document design and cultural and media studies, the authors offer qualitative andquantitative data in support of their argument.